O acervo do Hospital Dr. Stich: um patrimônio do município de São Marcos/RS (1933-1980): memória e pertencimento - Perozzo, Laura Cardozo (My University, 2021)
This research intertwined the narratives of the doctor from São Marcos Nyldo Sander Stich with the collection of a hospital in that city, currently deactivated and a doctors' offices, belonging to the interviewee's family, in an attempt to preserve the history of the city through the hospital heritage of the Stich genealogy. Throughout this research, Nyldo's memories and experiences, about his past and his family, with the stories of his adoptive father Frederico and his generatrix, Lúcia, as well as the Dr. Stich Hospital, make sense, based on the analysis of documentation and items available in the attic of the old hospital. This research aimed to build a narrative for health in the city of São Marcos, RS, based on the analysis of the documentation. To achieve it, oral history was used, theorized by the concept of representation, by Chartier, 1994, and memory and identity, by Candaü, 2018. It also made use of classification by support of the collection, using studies in the area of preservation and conservation of collections. Several products were created from the constitution of this narrative. The first is the document arrangement, created from the organization and categorization by supports of the collection available in the hospital's attic. With the collection, comes the second product, which is an exhibition of heritage education with items that show the important moments in the hospital's history. The third product was a Notebook of Memories, in which patients who currently attend the area of doctors' offices, on the ground floor of the building, they can write their memories about. Finally, chronological charts were made with the trajectory of Frederico, Lucia, Nyldo and the events that marked the history of Hospital Dr. Stich. Thus, this study seeks to enable the safeguarding of family heritage, but also to understand the relationships between the individual and the collective, in an attempt to preserve the history and heritage of the São Marcos region, through the transversality presented by the theme of health. [resumo fornecido pelo autor]
Esta pesquisa entrecruzou as narrativas do médico são-marquense Nyldo Sander Stich com o acervo de um hospital da referida cidade, hoje desativado e espaço de consultórios médicos, pertencente à família do entrevistado, na tentativa de preservar e conservar a história da cidade por meio do patrimônio hospitalar da genealogia dos Stich. Ao longo desta pesquisa, as memórias e vivências de Nyldo, sobre seu passado e de sua família, com as histórias de seu pai adotivo Frederico e sua geratriz, Lúcia, bem como do Hospital Dr. Stich, ganharam sentido, a partir da análise da documentação e dos itens disponíveis no sótão do antigo hospital. Esta pesquisa teve como objetivo construir uma narrativa para a saúde no município de São Marcos, RS, a partir da análise da documentação. Para tal, foi feito uso da história oral, teorizada pelo conceito de representação, de Chartier (1991), e de memória e identidade, de Candau (2018). Também fez uso da classificação por suporte do acervo, utilizando os estudos na área de preservação e conservação de acervos. Diversos produtos foram criados a partir da constituição dessa narrativa. O primeiro deles é o arranjo documental, criado a partir da organização e categorização por suportes do acervo disponível no sótão do hospital. Com o acervo, surge o segundo produto, que é uma mostra de educação patrimonial com os itens que apresentam importantes momentos da história do hospital. O terceiro produto foi um Caderno de Memórias, no qual os pacientes que frequentam atualmente a área de consultórios médicos, no andar térreo do prédio, podem escrever suas memórias sobre o espaço. Para finalizar, foram feitos quadros cronológicos com a trajetória de Frederico, Lúcia, Nyldo e os eventos que marcaram a história do Hospital Dr. Stich. Com isso, este estudo busca possibilitar a salvaguarda do patrimônio familiar, mas também de compreender as relações existentes entre o individual e o coletivo, na tentativa de preservar a história e o patrimônio do município, por meio da transversalidade apresentada pela temática da saúde. [resumo fornecido pelo autor]
Keywords: Hospital Doutor Stich - São Marcos (RS) - História; Patrimônio cultural - São Marcos (RS); Memória coletiva; Conservação histórica; Doctor Stich Hospital - São Marcos (RS) - History; Cultural Heritage - São Marcos (RS); Collective memory; Historic conservation